Removable Partial Denture - Functional Impression Techniques: Review - Melo Neto, Clóvis Lamartine de Moraes; Turcio, Karina Helga; Dos Santos, Daniela Micheline; Goiato, Marcelo Coelho (Prague medical report, 2023)
The objective of this article is to concisely review the main clinical techniques used to make the functional impression to manufacture a removable partial denture. Through this review, the dentist can develop his clinical knowledge.
Keywords: Denture, Partial, Removable; zubní náhrady částečné snímatelné; lidé; Humans